The Crime of Importing Goods Prohibited Under Trade Law - Natio, Ezra; Panjaitan, Saut Parulian; Ikhsan, Rd Muhammad (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research focused on the restriction of specific commodities from being brought into Indonesia and the implementation of regulations aimed at tackling the illegal activity of importing these prohibited products. Analyses are conducted on secondary sources of information, including statutes, books, and periodicals, in accordance with a juridical-normative research approach and conceptual approach. The research demonstrates that the limitation on importing specific commodities into Indonesia is intended to safeguard the interests of the nation and state. The forbidden goods encompass items that have the potential to disrupt military and security, pose risks to human health, cause harm to the environment, disrupt industry, trade, and finance, and damage cultural products. The Minister of Trade Regulation No. 18 of 2021, along with the Regulation of the Minister of Trade No. 40 of 2022, clearly states the precise commodities that are prohibited. Law enforcement against importing prohibited items uses administrative and criminal penalties. The imposition of import duties and the confiscation of merchandise are examples of administrative sanctions. Criminal sanctions are governed by articles 110 and 112 of Law No. 7 of 2014, which establish the provisions for cumulative criminal sanctions and penalties. Furthermore, these enforcement measures may be harmonized with customs regulation. In general, this research provides insight into the legal mechanisms implemented to enforce the prohibitions on specific imported products in Indonesia, as well as the underlying justifications for such restrictions, to safeguard national interests.